Analisis Kelayakan Usahatani Padi (Oryza sativa L.) Varietas Ciherang di Desa Bontomatene Kecamatan Turatea Kabupaten Jeneponto - Yusuf, Andi Muh.; Syafruddin, Reni Fatmasari; Asriadi, Andi Amran (MuJAgri: Musamus Journal of Agribusiness, 2024)
The purpose of this study was to determine the income and feasibility of the Ciherang variety of rice farming business. The location of the study was determined by purposive sampling. The sample was taken as many as 35 people who work as rice farmers. The analysis methods used were cost analysis, revenue, income and feasibility. The results of the research show that the average value of total effort Rp. 8,307,117 per planting season, obtaining a total of Rp. 39,397,338 per planting season and an income of Rp. 31,063,169 per planting season. Ciherang rice farming has an R/C ratio of 4.74> 1, meaning that Ciherang rice farming is feasible.